RESPON DOSIS PUPUK KANDANG KAMBING TERHADAP PERTUMBUHAN DAN HASIL TANAMAN MENTIMUN (Cucumis sativus L.) VARIETAS HIBRIDA - Dewi, Wahyu Wardiana (Universitas Islam Balitar, 2016)
This research is aimet to known the responsed of cucumber plant (Cucumis sativus L.), the good means for the growth and yield of cucumber (Cucumis sativus L) of the hybrid varieties doses of good means. This study uses a randomized block design (RAK) with one factor and 5 replications. The main factors, namely: goat manure. First repeat that: without fertilizer (P0), manure goat 10 ton / ha (P1), manure goat 20 ton / ha (P2), manure goat 30 ton / ha (P3), and the latter is manure goat 40 ton / ha (P4). The parameters observed were plant height, leaf number, fruit weight, fruit length and diameter of the fruit. Data analysis by using analysis of variance (ANOVA), if the effect followed by Least Significant Difference Test (BNT). The results based on the analysis of variance showed that: 1) Treatment of manure goat (P) significantly affected the growth and yield of cucumber plants include all the parameters of observation starting plant height, leaf number, fruit weight, fruit length and fruit diameter. Dose goat manure 40 t / ha is the best concentration to produce the highest average values for all parameters. The lowest value of all parameters are shown on the dose P0 (without manure goat / control).